(untitled) (Research, Society and Development, 2022)
The significant increase in the elderly population, in all countries, is related to the high estimate of time and duration of life. Concomitantly with the consequences of aging, cases in which family members and relatives have difficulties in caring for their elderly become increasingly common, referring them to institutions called Long Stay Institutions for the Elderly (ILPI). This article is a literature review, from original documents, collected through the Bireme, Scielo, Google Scholar databases and the theses and dissertations database that were published between the years 2013 to 2022. The objective of this review is, therefore, to identify in the existing literature, reports on the high rate of depression in institutionalized elderly, when compared with elderly in home care (CDM). The elderly population in the world has been increasing due to different factors, among them, we have the increase in life expectancy. Following the world scenario, Brazil also presents an aging population and linked to this new context, attention is needed for the care and quality of life of our elderly. The present study found a high prevalence of depressive symptoms in institutionalized elderly and in the physical and social domains, they showed dissatisfaction with their quality of life. In this way, it becomes necessary to overcome the challenges imposed by the institutionalization factor. With this, we conclude that the promotion of a stimulating environment, with varied activities, collective and appropriate to the sociocultural profile, provides preservation of physical and mental capacity, reduces the prevalence of signs and symptoms of depression and enhances the quality of life.